A feasibility study of goal-directed network-based real-time fMRI neurofeedback for anhedonic depression - Wang, Xiaoxia; Zhou, Xiaoyan; Li, Jing; Gong, Yushun; Feng, Zhengzhi (Frontiers in Psychiatry, 2023)
Anhedonia is a hallmark symptom of depression that often lacks adequate interventions. Translational gap remains in clinical treatments based on neural substrates of anhedonia. Our pilot study found that depressed individuals depended less on goal-directed (GD) reward learning (RL), with reduced reward prediction error (RPE) BOLD signal. Previous studies have found that anhedonia is related to abnormal activities and/or functional connectivities of the central executive network (CEN) and salience network (SN), which both belong to the goal-directed system. In addition, it was found that real-time functional magnetic resonance imaging (rt-fMRI) neurofeedback (NF) could improve the balance between CEN and SN networks in healthy individuals. Therefore, we speculate that rt-fMRI NF of the CEN and SN networks associated with the GD system may improve the depressive and/or anhedonic symptoms. Therefore, this study (1) will examine individuals with anhedonic depression using GD-RL behavioral task, combined with functional magnetic resonance imaging and computational modeling to explore the role of CEN/SN network deficits in anhedonic depression;(2) will utilize network-based rt-fMRI NF to investigate whether it is feasible to the 删除[wxx]: , which 删除[wxx]: a 删除[wxx]: could be improved by rt-fMRI NF of CEN and SN networks related to the GD system 删除[wxx]:regulate the differential signals of CEN/SN brain network of GD system through rt-fMRI NF to alleviate depressive and/or anhedonia. This study highlights the need to elucidate the intervention effects of rt-fMRI NF and the underlying computational network neural mechanisms.